(untitled) (Boletin Médico de Postgrado, 2020)
Guillain Barré Syndrome (GBS) is characterized by acute or subacute manifestation of peripheral nervous system alterations such as flaccid paralysis and arreflexia, which can eventually be life-threatening and/or become chronic if specific treatments are not established in a timely manner. The main causes of GBS are attributed to infectious agents which trigger an autoimmune response that affect both the myelin and the axon. GBS is the most frequent cause of flaccid paralysis in the pediatric population. The present investigation characterized the GBS in patients admitted to the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga in the period 2010 to 2016.